International law - Shaw, Malcolm N. (Cambridge Univ. P CambridgeGB, 2003)
Provides a comprehensive introduction to the subject of international law. Looks at inter-state courts and tribunals. Examines international humanitarian law and arbitration tribunals set up for dispute settlement. Focuses on the role of international institutions such as the WTO in resolving conflicts. Examines the prosecution of individuals for violations of international law. Covers the events in Kosovo and Iraq and analyses the questions of humanitarian intervention and the role of the UN.